Enigmacursor mollyborthwickae, a neornithischian dinosaur from the Upper Jurassic Morrison Formation of the western USA - Susannah C. R. Maidment; Paul M. Barrett (Royal Society Open Science)
Although their remains have been known since the 1870s, the small, bipedal ornithischian dinosaurs from the Upper Jurassic Morrison Formation of the western USA remain poorly known. The historic type specimens are incomplete and poorly preserved and have recently been designated as nomina dubia. Here, we describe a recently collected, partial but three-dimensionally preserved skeleton of a new small-bodied ornithischian from the Morrison Formation of Colorado, USA, that we name Enigmacursor mollyborthwickae gen. et sp. nov. The skeleton includes substantial portions of the axial and appendicular skeleton and, when scored into a phylogenetic analysis, is shown to be a non-cerapodan neornithischian, whose closest relative is Yandusaurus hongheensis from the Late Jurassic of China. The discovery of Enigmacursor enhances the diversity of ornithischian dinosaurs from the Morrison Formation and provides new information on their anatomy. In addition, it demonstrates that there is additional cryptic diversity of small-bodied Morrison Formation ornithischians, suggesting they were a more diverse component of these Late Jurassic ecosystems than was previously realized.